Large-male advantages associated with costs of sperm production in Drosophila hydei, a species with giant sperm. - Pitnick, S (1994)
Males of the fruit fly Drosophila hydei were found to produce 23.47 +/- 0.46-mm-long spermatozoa, the longest ever described. No relationship was found between male body size and sperm length. We predicted that if these giant gametes are costly for males to produce, then correlations should exist between male body size, rates of sperm production, and fitness attributes associated with the production of sperm. Smaller males were found to make a greater relative investment in testicular tissue growth, even though they have shorter and thinner testes. Smaller males were also found to (i) be maturing fewer sperm bundles within the testes at any point in time than larger males, (ii) require a longer period of time post-eclosion to become reproductively mature, (iii) mate with fewer females, (iv) transfer fewer sperm per copulation, and (v) produce fewer progeny. The significance of these findings for body size-related fitness and the question of sperm size evolution are discussed.